Innovative M-Learning with Automatic Feedback: Enhancing Language Acquisition for Level 2 Indonesian Foreign Speakers (BIPA) - Muzaki, Helmi; Susanto, Gatut; Widyartono, Didin; Bonde, Lossan; Moorthy, Thilip Kumar; Akhsani, Ilham (Journal of Languages and Language Teaching, 2024)
Indonesian has become the official language of the UN. Many BIPA students want to learn Indonesian online. However, online learning creates obstacles such as time differences between teachers and BIPA students, internet connections, and providing less than optimal feedback. This research aims to develop m-learning with automatic feedback for BIPA level 2 learners. This research uses a 4D development model: define, design, develop and deploy. This study's instrument is  a questionnaire distributed to 2 validators and 18 BIPA learners. The results of this study are m-learning products that minimize internet connections; once installed, students only need to be connected to the internet when working on questions. In addition, m-learning is also equipped with automatic feedback that appears immediately after students answer questions. The results of the product trial show that students can use m-learning to learn anytime and anywhere, including in areas with minimal internet access. Automatic feedback in m-learning also helps students learn independently because they do not need to wait for feedback from teachers. The automatic feedback in M-learning is only for listening and reading questions while speaking and writing questions are still in the form of answer keywords or assessment rubrics that the teacher must correct. Based on expert validation and product trials with an average score of 88.8, we conclude that the development of m-learning is suitable for BIPA level 2 students.